MANAJEMEN PERBANKAN BERBASIS NILAI: DAMPAK PADA PENGEMBALIAN PEMEGANG SAHAM - Ahfi Nova Ashriana (Media Mahardhika, 2020)
In this study, we analyzed the drivers of Total Shareholder Revenue (TSR) at commercial banks and evaluated whether non-adopter TSR performed better by Value-Based Management (VBM) banks. TSR models using data from 132 commercial banks registered in Europe and North America are estimated. First, we point out that banking institutions that have publicly implemented VBM in their MCS outperform non-VBM banks. VBM adopters produce annual TSR with an average of 5.8 percentage points. In terms of profitability, growth and liquidity, they also outperform non-VBM banks. Second, we note that banking companies concentrate on key performance indicators (KPIs) such as cost-of-income ratios which are suboptimal TSR indicators. We propose the implementation of indicators closer to TSR, such as asset repayment or the provision of loan losses. In their MCS, to date few banks have considered such KPIs (10 percent -45 percent). The shift to KPIs we propose can further improve the performance of VBM adopters. Our findings stabilized before and after the 2008 financial crisis when we monitored macroeconomic factors.